Factors Influencing Nurses’ Compliance in the Implementation of Patient Safety at Rumah Sakit Islam Gorontalo - Mevianri F Peleng; Andi Akifa Sudirman; Sabirin B. Syukur (Universitas Muhammadiyah Palu, 2026)
Patient safety is a top priority in healthcare services and constitutes the first step in improving service quality. Compliance with patient safety implementation is influenced by several factors, including length of work experience, knowledge, and nurses’ motivation. This study aimed to determine the factors influencing nurses’ compliance in the implementation of patient safety at Rumah Sakit Islam Gorontalo. This study employed a correlational quantitative design with a cross-sectional approach. The sampling technique used was non-probability sampling with total random sampling, involving 41 respondents. Data were collected using a questionnaire sheet. The results of the study using the Chi-square (x²) statistical test showed that there was a relationship between work experience factors (p = 0.032), knowledge (p = 0.045), and motivation (p = 0.010) with compliance in the implementation of patient safety at Rumah Sakit Islam Gorontalo. The study suggests the need to improve evaluation and follow-up regarding compliance with patient safety implementation in the inpatient wards of Rumah Sakit Islam Gorontalo.